Effect of 12 weeks of duet free routine training on physiological and technical variables in artistic swimmers - Komori, Y.; Okamoto, Y.; Shimura, Y.; Hoshino, S.; Inoue, M. (The Journal of Physical Fitness and Sports Medicine, 2018)
The duet free routine (FR) does not require predetermined elements to perform; a much greater emphasis is placed on the creativity of the choreography and movement. Judgement of the duet FR was evaluated on the basis of execution, artistic impression, and difficulty. Therefore, physiological and technical factor are important for Artistic swimmers in performing the duet FR. The purpose of this study was to examine the effect of duet FR training on physiological and technical variables in elite artistic swimmers. [Methods] Two artistic swimmers who represented Kyoto prefecture at the National Athletic Meet in Japan participated in this study. The performance indicators of the duet FR were heart rate (HR) during performance, rate of perceived exertion (RPE), self-evaluation of technical movements, and judgement of the duet FR by the referees. These indicators were measured 3 times during the 12-week 2017 competition period. [Results] No differences were observed in the HRs and RPE in the duet FR performed from test1 to test3. However, the self-evaluation of the technical scores were higher and the judgement scores by the referees was better in test3 than in test1. [Conclusions] These findings show that during the competition-period training, improved evaluation scores for technical movements and performance as judged by the referees are required. This study suggest the importance of enhancing the quality of movements in the performance during the competition period.